THE OBJECTIVITY OF THE BUSINESS COMPETITION SUPERVISORY COMMISSION IN DECIDING BUSINESS COMPETITION CASES IN INDONESIA - Rifqon Khairazi (Faculty of Law, Universitas Lampung, 2021)
This study discusses the commission board’s objectivity in a trial while deciding a business court case. This study aims to identify the commission board and investigators’ authority in a courthouse, and the fact that they are in the same institution as well as the concern. This study uses a type of normative research through a statutory approach and a conceptual approach. This research’s document source is obtained by tracing statutory regulations, especially those related to business competition. The research shows a relationship that can affect The Indonesian Competition Commission (ICC) decision regarding the extent of authority that ICC has, as contained in the provisions of Article 36 of Law No. 5/1999. This obscurity can provide legal loopholes that have potentially offer a wide range of unlawful authority for ICC. Therefore, the Government has to amend the current regulation.